Community Participation in Mampari Village, Balangan Regency Reducing Waste Using the 3R Method - Safitri, Gina; Adyatma, Sidharta; Angriani, Parida; Arisanty, Deasy; Saputra, Aswin Nur (Sustainability (STPP) Theory, Practice and Policy, 2024)
Every day waste production is increasing along with the increase in the number of products and people's consumption patterns. What must be done to overcome the increase in waste volume is to reduce the volume of waste from the source through waste management from the community itself. The problem in community participation regarding waste management using the 3R method in Mampari Village, Balangan Regency is what form of community participation in waste management and the level of participation in community waste management. Research on waste reduction using the 3R method in Mampari Village aims to: (1) describe the forms of community participation in Mampari Village. (2) describe the level of participation of the Mampari Village community, data collection includes interviews, observation and documentation, while data analysis uses quantitative descriptive techniques. Based on the research results, one form of community participation in efforts to reduce waste using the 3R method is by providing contributions in the form of energy, goods and money as well as community service and participating in waste management. Apart from that, they also hold community meetings once a month, which are attended by several residents. The level of community participation that occurs in Mampari Village according to the category is low, the only community members who participate are village mobilizers consisting of 10-15 people so that the implementation of waste management is very lacking and still not optimal